Integrated activities of two alternative sigma factors coordinate iron acquisition and uptake by Pseudomonas aeruginosa. Issue 6 (26th October 2017) - Edgar, Rebecca J.; Hampton, Georgina E.; Garcia, G. Patricia Casas; Maher, Megan J.; Perugini, Matthew A.; Ackerley, David F.; Lamont, Iain L.
Summary: Alternative sigma (σ) factors govern expression of bacterial genes in response to diverse environmental signals. In Pseudomonas aeruginosa σ PvdS directs expression of genes for production of a siderophore, pyoverdine, as well as a toxin and a protease. σ FpvI directs expression of a receptor for ferripyoverdine import. Expression of the genes encoding σ PvdS and σ FpvI is iron‐regulated and an antisigma protein, FpvR20, post‐translationally controls the activities of the sigma factors in response to the amount of ferripyoverdine present. Here we show that iron represses synthesis of σ PvdS to a far greater extent than σ FpvI . In contrast ferripyoverdine exerts similar effects on the activities of both sigma factors. Using a combination of in vivo and in vitro assays we show that σ FpvI and σ PvdS have comparable affinities for, and are equally inhibited by, FpvR20 . Importantly, in the absence of ferripyoverdine the amount of FpvR20 per cell is lower than the amount of σ FpvI and σ PvdS, allowing basal expression of target genes that is required to activate the signalling pathway when ferripyoverdine is present. This complex interplay of transcriptional and post‐translational regulation enables a co‐ordinated response to ferripyoverdine but distinct responses to iron. Abstract : In Pseudomonas aeruginosa production and uptake of a siderophore pyoverdine is regulated through the combined actions of two sigma factors, σ FpvI and σ PvdS, and an antisigma protein FpvR20 . We show that FpvR20 has similar affinity for both sigma factors. The amount of FpvR20 is less than the total amount of sigma factor protein, allowing basal expression of target genes, and FpvR20 is degraded in the presence of pyoverdine increasing activity of the sigma factors.